(3GdhUGjG GdebOSIs - (3Rjf GdNhGaj, eMeO Hf eMeO Hf eMeO, J(B838(3g`s
(3ChdgG (B:s
(3CeG HYO MeO Gddg hGdUdGI hGdSdGe Ydi QShdg eMeO hBdg agPg hUjI dCUMGHj hChdGOj GdPjf JGHhG Edi Gddgs
(3BNQgG (B:s
(3hGYde CfJ GdJQJjH aEfj eG cJHJ Ydi GdJHhjH hCfJ TGgOJ MGdj hJhRY HGdj CSCd Gddg Jhajb GdYed HebJVGgGs
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B825(3g` , haj BNQg fbhd aj GdCOHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 46s
(3eYLe GdeDdajf(B: 3 / 641s
(3cTa GdXfhf(B: 2 / 2012s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs